Burn Care in the 1800s. Issue 1 (January 2015) - Hattery, Eleanor; Nguyen, Tiffany; Baker, Aaron; Palmieri, Tina
<x xml:space="preserve">Abstract</x> The 1800s show a wide range of both understanding and misinterpretation of the pathophysiology and treatment of burns. The objective of this paper was to describe the key advancements in the study and treatment of burns in the 1800s. We reviewed primary and secondary sources of ancient to modern burn care manuscripts. Prior to the 1800s, burn care was different iterations of poultices and oils placed over acute burns in the hope the patient would survive. The 1800s showed the discoveries of the Curling and Marjolin's ulcers as well as the first understanding of inhalation injury and advancements in skin grafting, leading to further understanding of the disease process.